Effects of introducing rest intervals in functional fitness training - Hernández-Lougedo, Juan; Cimadevilla-Pola, Eduardo; Fernández-Rodríguez, Tomás; Guodemar-Pérez, Jesús; Otero-Campos, Álvaro; Lozano-Estevan, María Del Carmen; Cañuelo-Márquez, Ana María; de Jesús-Franco, Fernando; Garnacho-Castaño, Manuel V.; García-Fernández, Pablo; Maté-Muñoz, José Luis (MDPI, 2022)
Background: Functional Fitness Training (FFT) is a new exercise modality prioritizing functional multi-joint movements executed at high intensity as a circuit. Objective: To examine the impacts of introducing rest intervals in a FFT workout compared to “rounds for time” (RFT) FFT. Materials and Methods: Participants were 25 resistance-trained adults who completed two FFT workouts 1 week apart. The study design was crossover such that in a given session half the participants completed the standard and the other half the adapted FFT (FFTadapted). The workouts consisted of the same exercises (circuit of four rounds of exercises), but one (FFTadapted) included preset rest intervals (three sets of 1 min after each completed round). Before and after the workouts, countermovement jump ability and blood lactate were measured. Heart rate (HR) and ratings of perceived exertion (RPE) were measured post-exercise. Results: For both the standard and adapted protocols, mean HR was 90% age-predicted maximum. Final RPE was also similar for both workouts (~15–15.5) and indicated a “hard” work intensity. Both FFTs took the same time to complete (~13 min). Furthermore, no significant differences were observed in jump ability between FFTs. In contrast, lactate (15.11 ± 3.64 vs. 13.48 ± 3.64 mmol·L−1, p < 0.05), measured 3 min post-exercise, was significantly lower in FFTadapted. Conclusions: In FFTadapted, there was a significant reduction in RPE and blood lactate concentrations after exercise, while there were no significant differences in either HR or jumping ability, compared to a FFT workout in RFT methodology.
Keywords: countermovement jump; high-intensity training; lactate; muscular fatigue; rate of perceived exertion; Scopus; JCR